Different sagittal angles and moments of lower extremity joints during single-leg jump landing among various directions in basketball and volleyball athletes - Sinsurin, K.; Vachalathiti, R.; Jalayondeja, W.; Limroongreungrat, W. (Journal of Physical Therapy Science, 2013)
The purpose of this study was to assess the sagittal angles and moments of lower extremity joints during single-leg jump landing in various directions. Subjects: Eighteen male athletes participated in the study. Methods: Participants were asked to perform single-leg jump-landing tests in four directions. Angles and net joint moments of lower extremity joints in the sagittal plane were investigated during jump-landing tests from a 30-cm-high platform with a Vicon™ motion system. The data were analyzed with one-way repeated measures ANOVA. Results: The results showed that knee joint flexion increased and hip joint flexion decreased at foot contact. In peak angle during landing, increasing ankle dorsiflexion and decreasing hip flexion were noted. In addition, an increase in ankle plantarflexor moment occurred. Conclusion: Adjusting the dorsiflexion angle and plantarflexor moment during landing might be the dominant strategy of athletes responding to different directions of jump landing. Decreasing hip flexion during landing is associated with a stiff landing. Sport clinicians and athletes should focus on increasing knee and hip flexion angles, a soft landing technique, in diagonal and lateral directions to reduce risk of injury.